Exploring the prehospital care competency of emergency and trauma department personnel at SASMEC@IIUM - Nurumal, Mohd. Said; Jamaludin, Thandar Soe Sumaiyah; Mat Isa, Rif'atunnailah; Che Hasan, Muhammad Kamil; Abdul Hamid, Abdul Alif; Win, Kyu Kyu; Noviani, Wulan (Media Shed, 2024)
Trauma is a leading global cause of mortality, with road accidents alone resulting in over 1.3 million deaths annually and a significant impact in Malaysia. Emergency Medical Services (EMS) play a crucial role in providing prehospital care, reducing mortality rates by 25%, yet the competency of Emergency and Trauma Department (ETD) personnel remains underexplored. This qualitative study aimed to explore the prehospital care competency of Emergency and Trauma Department (ETD) personnel at the Sultan Ahmad Shah Medical Centre, International Islamic University Malaysia (SASMEC@IIUM). A purposive sampling method was employed to recruit ten participants, including medical officers, assistant medical officers, and staff nurses, who were directly involved in prehospital care. Semistructured in-depth interviews were conducted to gather data on the participants' perspectives regarding their knowledge, skills, and readiness for prehospital care involvement. The findings revealed three main themes: Prehospital Care Stabilization, Challenges in Prehospital Care, and Improvement Aspects in Prehospital Care. Key recommendations include the implementation of standardized protocols, strengthening of team communication and coordination, enhancement of staff competency through continuous education and training, and advocacy for increased financial support. Addressing these recommendations can help enhance the quality and efficiency of prehospital care services at SASMEC@IIUM, ultimately improving patient outcomes and satisfaction.